THU0278 The effect of anti-tumor necrosis factor therapy with golimumab on radiographic progression in definite ankylosing spondylitis: 4-year results. (23rd January 2014) - Braun, J.; van der Heijde, D.; Hermann, K.-G.; Baraliakos, X.; Deodhar, A.; Beutler, A.; Mack, M.; Xu, W.; Hsu, B.; Inman, R.
Abstract : Background: Three clinical trials in which structural spinal changes in patients with ankylosing spondylitis (AS) treated with tumor necrosis factor (TNF) antagonists over 2 years (yrs) were assessed in comparison to a historical cohort have indicated that such therapy may not alter radiographic progression as quantified by the modified Stokes Ankylosing Spondylitis Spinal Score (mSASSS). Longer-term data are scarce. Objectives: The purpose of this study is to assess the effects of the anti-TNF agent golimumab (GLM) on radiographic progression in patients (pts) with AS through 2 and 4 yrs of treatment. Methods: Pts (n=356) were randomly assigned (1:1.8:1.8) to subcutaneous injections of PBO, GLM 50mg, or GLM 100mg q4weeks (wks). At wk16, pts in the PBO or 50mg groups with <20% improvement in both total back pain and morning stiffness entered early escape (EE) to GLM 50 or 100mg, respectively. At wk24, pts still receiving PBO crossed over (CO) to GLM 50mg. Lateral view radiographs of the cervical and lumbar spine were performed at baseline, wk104 and wk208. Radiographs were read by 2 independent, central, trained readers using mSASSS methodology (0=normal; 1=erosion, sclerosis, or squaring; 2=syndesmophyte; 3=bridging syndesmophyte). The mSASSS ranges from 0-72. Results: Among all randomized pts, median time since first AS symptoms was 11.0 yrs. Treatment groups were comparable with regard to age, gender, BASDAI, BASFI, BASMI, CRP, mSASSS, and baseline syndesmophytes. Overall mean changes in mSASSS were 1.1 at wk104, with no obvious treatment group differences, and 3.6 at wk208, with numerically larger changes in the GLM 100mg group (Table). Due to wide distribution of change values, the numerical differences in mean change in mSASSS for the 100mg group or for the 19 radiographically evaluable pts who dose-escalated from 50 to 100mg via EE (data not shown) are not significant by ANOVA on the van der Waerden normal scores. At wk 104 and wk 208, 23.1% and 35.1% of pts had a definitive change (>2 points) in mSASSS. Conclusions: Changes in mSASSS from baseline to wk104 and wk208 indicated that anti-TNF treatment with GLM does not inhibit radiographic progression in the spine of pts with AS. Disclosure of Interest: J. Braun Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, D. van der Heijde Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, K.-G. Hermann Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, X. Baraliakos Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Deodhar Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Beutler Employee of: Janssen Research & Development, LLC, M. Mack Employee of: Janssen Research & Development, LLC, W. Xu Employee of: Janssen Research & Development, LLC, B. Hsu Employee of: Janssen Research & Development, LLC, R. Inman Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study